2015
DOI: 10.4049/jimmunol.1401852
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Disulfide Bonds of Helicobacter pylori GroES Are Critical for IL-8 Secretion via the TLR4-Dependent Pathway in Gastric Epithelial Cells

Abstract: Helicobacter pylori GroES (HpGroES), a potent immunogen, is a secreted virulence factor that stimulates production of proinflammatory cytokines and may contribute to gastric carcinogenesis. HpGroES is larger than other bacterial orthologs because of an additional C-terminal region, known as domain B. We found that the HpGroES-induced IL-8 release by human gastric epithelial cells was dependent on activation of the MAPK and NF-κB pathways. HpGroES lacking domain B was unable to induce IL-8 release. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Previous studies have demonstrated that Hp GroES binds TLR4 on the cell surface25. To further establish the binding abilities of WT and mutant proteins to TLR4 on the cell surface, KATO-III cells were incubated with 0.05 μM WT or histidine mutants, and the localization of Hp GroES and TLR4 determined via confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that Hp GroES binds TLR4 on the cell surface25. To further establish the binding abilities of WT and mutant proteins to TLR4 on the cell surface, KATO-III cells were incubated with 0.05 μM WT or histidine mutants, and the localization of Hp GroES and TLR4 determined via confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The cytokine plays a role in gastric mucosal injury caused by H. pylori and is correlated with the development of chronic gastritis16. Domain B of Hp GroES contributes to Hp GroES-induced IL-8 secretion through a TLR4-dependent mechanism25. Domain B displays a unique conformational loop structure generated by two disulfide bonds referred to as the four-cysteine ring (4CR) motif.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations